A comparative analysis of the outcome of unilateral laminotomy and conventional laminectomy in patients with single-level degenerative lumbar spondylolisthesis: a single-center retrospective study 104 patients on postoperative pain and functional disability - Li, Yan; Zhu, Congcong (Frontiers in Surgery, 2025)
ObjectiveTo compare the clinical and radiologic outcomes of unilateral laminotomy vs. conventional laminectomy for decompression in patients with single-level degenerative lumbar spondylolisthesis.MethodsThis retrospective study included 104 patients who underwent decompressive surgery for single-level degenerative lumbar spondylolisthesis at a single institution. Clinical outcomes were assessed using the Oswestry disability index (ODI) and the visual analog scale (VAS) for back and leg pain. Radiologic outcomes were evaluated by measuring translational motion, disc height, and epidural cross-sectional area on imaging.ResultsThe average age of patients was 58.95 years (range: 40–79). Both groups showed comparable VAS scores for lamb pain and complication rates. However, the unilateral laminotomy group had significantly lower VAS scores for back pain and ODI scores within the group. Improvements in these scores were more pronounced in the unilateral laminotomy group compared to the conventional laminectomy group, reflecting within-group comparisons. The unilateral laminotomy group also experienced less intraoperative blood loss and shorter surgical time. Radiographically, there were no significant differences (P > 0.05) in translational motion or disc height between the two groups. However, the traditional laminectomy group showed a larger epidural cross-sectional area. Postoperative complications were rare.ConclusionsBoth unilateral laminotomy and conventional laminectomy provide effective pain relief and adequate decompression for spinal stenosis. Unilateral laminotomy offers the advantage of reduce blood loss, shorter operative time, and lower VAS scores for back pain. Radiographically, the two procedures produce similar outcomes in terms of translational motion and disc height, although the traditional laminectomy group exhibited a larger epidural cross-sectional area. Despite this, VAS scores for leg pain were comparable between the two groups. Further studies are needed to compare the effects of surgical techniques at different lumbar levels.